THE KACHAMBA BROTHERS' BAND: a study of neo-traditional music in Malawi by Gerhard Kubik. University of Zambia, Institute for African Studies, Zambian Papers No. 9, P.O. Box 900, Lusaka, Zambia, 1974, pp. 75, x, plates, diagrams, bibliography, K2.50, £2.25 - Rycroft, David K. (International Library of African Music, 1975)
pages: 151-152
Keywords: African Music; Malawi